DEVELOPING ASSESSMENT AS LEARNING BASED ON PROBLEM-SOLVING TO PROMOTE UNIVERSITY STUDENTS' SKILLS IN CRITICAL-CREATIVE THINKING - Endah Tri Priyatni; Martutik Martutik (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
Assessment as learning is an assessment to guide and provide opportunities forparticipants to monitor and reflect critically on their learning processes and outcomes.This study aimed to produce assessments as learning based on problem-solving thatcould be used to improve university students' skills in critical-creative thinking and totest the validity, reliability, and effectiveness of the assessment. The research designused was a 4D model, which stands for 'defining, designing and developing, anddisseminating. The research data consisted of two categories, which were qualitativeand quantitative. The qualitative data were in the form of comments, criticisms, andsuggestions from the expert team specializing in assessment; the quantitative data werein the form of critical-creative skills scores of product users. Qualitative data sourceswere the expert assessment team, and quantitative data sources were the fourthsemester college students of the Indonesian Department, Faculty of Letters,Universitas Negeri Malang. The research findings show that the product was valid andreliable. Besides, the result of the test of effectiveness indicated that this assessmentcould improve university students' skills in critical-creative thinking.